2003
DOI: 10.4049/jimmunol.171.7.3442
|View full text |Cite
|
Sign up to set email alerts
|

IL-2-Activated CD8+CD44high Cells Express Both Adaptive and Innate Immune System Receptors and Demonstrate Specificity for Syngeneic Tumor Cells

Abstract: CD8+ T cells depend on the αβ TCR for Ag recognition and function. However, Ag-activated CD8+ T cells can also express receptors of the innate immune system. In this study, we examined the expression of NK receptors on a population of CD8+ T cells expressing high levels of CD44 (CD8+CD44high cells) from normal mice. These cells are distinct from conventional memory CD8+ T cells and they proliferate and become activated in response to IL 2 via a CD48/CD2-dependent mechanism. Before activation, they express low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 51 publications
(70 reference statements)
5
61
0
1
Order By: Relevance
“…15 The CTL activity of activated CD8 T cells against RMA, RMA-Rae-1␦ target cells was assessed at a ratio of 10 effector T cells to 1 target cell in a 4-hour 51 Cr-release assay. For redirected lysis experiments, day-4 activated CD8 T cells were preincubated with the indicated mAb (10 g/mL) for 15 minutes.…”
Section: Ctl Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The CTL activity of activated CD8 T cells against RMA, RMA-Rae-1␦ target cells was assessed at a ratio of 10 effector T cells to 1 target cell in a 4-hour 51 Cr-release assay. For redirected lysis experiments, day-4 activated CD8 T cells were preincubated with the indicated mAb (10 g/mL) for 15 minutes.…”
Section: Ctl Assaysmentioning
confidence: 99%
“…13,14 We have recently showed that CD8 ϩ CD44 hi T cells from normal mice possess characteristics of both T cells and NK cells. 15 These cells are activated in response to IL-2 alone and show self-reactivity in that they preferentially kill syngeneic tumor cells. Furthermore, CD8 ϩ CD44 hi T cells express NK receptors upon activation, and engagement of these NK receptors enhances the ability of the cells to lyse syngeneic tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…8 In prostate cancer patients, tumorderived exosomes downregulated NKG2D expression on circulating CD8 C T cells. 9 Recent NKG2D regulation studies showed that many cytokines influence NKG2D expression on CD8 C T and NK cells, including the NKG2D-promoting cytokines interleukin (IL)-2, IL-7, and IL-12 [10][11][12] ; the NKG2D-suppressing cytokines IL-4 and transforming growth factor-b; and interferon-g, at high levels. 13,14 However, the mechanisms of NKG2D regulation on CD8 C T cells remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the antigen-specific immune response, the host has an increase in cytokines, NK cells, macrophages and memory T cell activation. 65,66 These recruited immune effector cells can cause MHC independent killing of tumor cells and cytokines that result in a bystander T cell response 67 that can also control tumor growth 68 (Figure 1b). Moreover, the innate immune system can detect CMV DNA via toll-like receptor (TLR) 9 and cyclic GMP/AMP synthase (cGAS) catalyzing formation of stimulator of interferon genes (STING) followed by an upregulation of type I interferon responses 69,70 that may cause indirect killing of tumor cells.…”
Section: Mechanisms Of Action Of Anti-cmv Based Immunotherapymentioning
confidence: 99%